21st Century Education: Improving Students' Skills Using Cooperative Learning Models In Social Studies Learning - Buti Sarma Sitompul; Fizri Aspika Putri Pane; M. Dzaky Labib; Nur Adila; Sabilla Meliani Brutu; Eka Yusnaldi (Sean Institute, 2025)
The 21st Century skills-based cooperative learning model in Social Sciences learning aims to improve students' abilities in critical, collaborative, creative and communicative thinking through a more active and interactive approach. Education in the 21st century faces a number of significant challenges. The world of education has a big responsibility to respond to these challenges. In this century, students really need relevant competitive skills. Cooperative learning in the 21st century era will really help students develop the skills needed, namely critical thinking, communication, collaboration, creativity, or usually called 4C skills (Critical thinking, communication, collaboration, creative), so that when students have these skills students can improve their learning outcomes. This research uses a qualitative approach with library research methods using literature (material) obtained from books, journals, articles, the internet and various other sources. The research results show that the cooperative learning model in the 21st century era can increase students' knowledge and skills, so that the quality of education increases. Thus, educators can consider implementing the cooperative learning model .